Evaluation of Digital Learning Integration to Improve Junior High School Students' Digital Literacy - Liony Margareta; Rina Avatus Marheni; Heni Purwitasari (JINEA: Journal of Innovation in Education and Learning, 2025)
This study examines the role of digital literacy in mathematics education, focusing on students’ learning experiences with the Pythagorean Theorem and Linear Equations. Digital literacy, which includes the ability to search, evaluate, and synthesize online information, is increasingly vital in supporting effective learning. A total of 60 students participated in face-to-face lessons supported by digital applications such as Photomath, Microsoft Math Solver, and Mathway. Data were collected through classroom observation, worksheet analysis, documentation of interactions with digital tools, semi-structured interviews, and a validated digital literacy questionnaire covering three aspects: information searching, content evaluation, and knowledge assembly. The findings show that students achieved a very high level in information searching (80%), while content evaluation (75%) and knowledge assembly (70%) were categorized as high. These results highlight the effectiveness of digital tools in facilitating quick access to problem-solving procedures, but also reveal the need to strengthen students’ ability to critically evaluate and reconstruct knowledge. In conclusion, digital literacy is essential for enriching mathematics learning, enhancing engagement, and deepening conceptual understanding. However, instructional designs must emphasize critical and reflective thinking so that students can move beyond passive use of technology toward becoming active, independent, and critical problem-solvers in the digital era.